Peran Decision Support System dalam Mendukung Pengambilan Keputusan Keuangan pada Berbagai Skala Usaha (Kecil, Menengah, dan Besar) di Indonesia - Julius Andhika Prasetyo; Muhammad Rafly Dwi Desta; Haikel Bremana Gurusinga; Muhammad Rizal (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
The development of information technology has encouraged organizations of various business scales to utilize systems capable of supporting decision-making processes more effectively. However, many organizations have still faced challenges in making decisions due to the use of conventional methods that were less responsive to changes in the business environment. This study aimed to analyze the role of Decision Support Systems in supporting decision-making processes in small, medium, and large-scale businesses in Indonesia. The study employed a descriptive qualitative approach using a literature review method. Data were collected from various relevant secondary sources, including scientific journals, books, and other academic publications. The analysis was conducted through the processes of collecting, categorizing, and interpreting information related to the implementation of Decision Support Systems across different business scales. The findings indicated that Decision Support Systems contributed to improving the quality of decision-making by providing faster, more accurate, and data-driven information. In small-scale businesses, the system helped improve operational efficiency and resource management. In medium-scale businesses, it supported business planning and development through more comprehensive data analysis. Meanwhile, in large-scale businesses, the system was utilized to manage complex data, perform real-time monitoring, and generate strategic recommendations. Therefore, Decision Support Systems were proven to be important tools for enhancing business management effectiveness and organizational competitiveness in the digital era.